A novel data resource: Developing the Census 2021 Comprehensive Microdata and gaining insight on the minority ethnic population in Northern Ireland - Toner, Sinead; Foley, Brian; Colohan, Carmel; Drumm, Sinéad (International Journal of Population Data Science, 2025)
Objectives The Census 2021 Comprehensive Microdata (C21CM), comprising over 98% of person and household data from the last census in Northern Ireland, was developed to advance research across various themes. The large sample size supports valuable research on small population groups, in this case the minority ethnic population in Northern Ireland. Method The C21CM dataset is exclusively derived from Northern Ireland Census 2021 data, providing accredited research access to 1.87 million and 760 thousand person and household de-identified records, respectively. The data supports analysis to identify socioeconomic and health outcomes for the minority ethnic groups (MEGs) classified in the Census. Regression modelling is applied to investigate the likelihood of outcomes of interest (for example, being in employment) among the different MEGs, controlling for person-, household- and area-level factors. Engagement with the Racial Equality Subgroup, a representative body for MEGs in Northern Ireland, is important in shaping the research questions and ensuring relevance. Results We provide an overview of the quality assurance measures taken in developing the C21CM to ensure data accuracy and reliability. Additionally, we present the guidance document for researchers, which includes variable descriptions and instructions on accessing the data. The value of the C21CM is demonstrated by the research results providing new insight on the minority ethnic population in Northern Ireland, for example, whether there are differences in health, education, employment and housing outcomes between MEGs, and if so the extent of these differences. We explore the association between these outcomes and a range of demographic, socioeconomic and migration-related variables. Furthermore, with the C21CM providing household-level data, it enables us to present associated results and provide insight beyond the person level. Conclusion The C21CM is available through the Northern Ireland Statistics and Research Agency Secure Environment. We highlight its current and potential applications; findings from this research are intended to support the strategic approach to racial equality in Northern Ireland beyond 2025, overseen by The Executive Office government department.